72=-1.33x

Simple and best practice solution for 72=-1.33x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 72=-1.33x equation:


Simplifying
72 = -1.33x

Solving
72 = -1.33x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '1.33x' to each side of the equation.
72 + 1.33x = -1.33x + 1.33x

Combine like terms: -1.33x + 1.33x = 0.00
72 + 1.33x = 0.00

Add '-72' to each side of the equation.
72 + -72 + 1.33x = 0.00 + -72

Combine like terms: 72 + -72 = 0
0 + 1.33x = 0.00 + -72
1.33x = 0.00 + -72

Combine like terms: 0.00 + -72 = -72
1.33x = -72

Divide each side by '1.33'.
x = -54.13533835

Simplifying
x = -54.13533835

See similar equations:

| 72=-1.33 | | 3(5x-3)+2(14-2x)-2(5x+2)=-1 | | 8-(-3x)=x | | 11=5y+-3y | | -1.1-(-10.1)= | | (6y+8)-(3+5y)=8 | | 400x= | | 15+h=10 | | 3(8)=n(0.08)(300) | | 8x+4=x-14 | | 13x^3-36x=-12x^2 | | 2x-3xm-3x*4=-2m-8 | | 4x-5x-3=0 | | 2x+8y=x-2y | | Y=-5/3-5 | | 2x--2=2 | | 3.4=15.9-5w | | 5x^2+3x=2x(x+6) | | 6p+6=5p+14 | | z+0.9=3.1 | | x(2-12-3m)=-8-2m | | r(1.4+35)=436.60 | | 4x-7=59-7x | | x-1/4=5 | | 2xc+-1c^2x+x=-10+5c | | 4x-3-4=24 | | x+2cx-c^2x=-10+5c | | X^2-25-144=0 | | (6*6-3*3*3)/7 | | (u^4/-2w^2)^2 | | -56=y-49 | | -67=-32n+29 |

Equations solver categories